(untitled) (Journal of Economic Research & Business Administration, 2016)
The competitiveness of the domestic goods depends largely on adjusted system of promotion. An important role in the promotion of products in developed countries, branding technology Kazakhstan has almost no circulated branding. In the article discusses the importance of the brand to improve competitiveness of domestic producers, considered theoretical and practical aspects of branding. Give a definition the concepts of «branding», «management of branding ». Determined difference brand from the trademark.In Kazakhstan, are not so not so many companies that have implemented brand management, so the article defines the possibility of it’s introduction are justified the positive effects are justified. Considered negative factors that hinder the development of brand management of Kazakhs enterprises. Suggests the ways improve the competitiveness of domestic producers in the area of sales promotion, considered the laws creating the company’s brand.